(untitled) (Research, Society and Development, 2025)
Pregnancy is a period of extreme importance in a woman’s life and her family’s, with prenatal care being essential for promoting maternal and fetal health. Prenatal care goes beyond mere medical check-ups; it’s a continuous process of care aimed at ensuring the well-being of both mother and baby from conception to delivery, providing support and guidance through knowledge exchange, thereby facilitating this experience. The objective of this experience report is to promote awareness and education about prenatal care and reaffirm the bond between pregnant women and their families with the Basic Health Unit. According to the guidelines of the Brazilian Ministry of Health, a minimum of six prenatal visits spread across the gestational trimesters is recommended, ensuring adequate monitoring during this crucial period. These visits provide guidance on proper nutrition, healthy lifestyle practices, pregnancy care, labor, postpartum care, breastfeeding, and family planning. Additionally, various screening tests are conducted to monitor the health of the mother and fetus, including blood tests to assess hemoglobin levels, identify potential infections, and determine the mother’s blood type and Rh factor. Imaging exams, such as ultrasounds, are used to monitor fetal growth and development and detect congenital anomalies.